The first experience in normothermic ex vivo kidney perfusion (case report) - A. V. Shabunin; M. G. Minina; P. A. Drozdov; V. M. Sevostyanov; N. V. Grudinin; V. K. Bogdanov; D. A. Bankeev; E. A. Tenchurina (Вестник трансплантологии и искусственных органов)
Objective: to assess if normothermic ex vivo machine perfusion (NMP) of a kidney from an expanded criteria donor (ECD) is feasible and safe.Materials and methods. NMP of the right kidney from an ECD was performed on a device developed at Botkin Hospital. A solution based on donor’s blood with the addition of Ringer’s lactate solution and human albumin was used for perfusion. The temperature in the circuit was maintained at 37 °C. Perfusion lasted for 203 minutes, after which the renal resistive index was almost halved from 0.33 to 0.16. 120 ml of urine was obtained.Results. The right kidney was successfully transplanted after perfusion. There was immediate function of the right renal graft in the postoperative period. The recipient’s serum creatinine level was 530 μmol/L on day 1 following transplantation and 170 μmol/L on day 14 of discharge. The left kidney was preserved by static cold storage and further transplanted to the recipient.Conclusion. The use of NMP to preserve grafts obtained from ECDs is safe and feasible in clinical practice. Further studies are required to determine the clear indications for its use and to formulate an optimal procedure for its implementation.